Participants' perceptions of the effectiveness of an in-house training program for new mid-level leaders at DeVry University - Carter, Catherine J., author; Davies, Timothy Gray, advisor; Mayers, Patrick, committee member; Harbour, Clifford P., committee member; Morgan, George A., committee member (Colorado State University. Libraries, 2005)
The role of the mid-level academic administrator is one that is constantly expanding and evolving to meet the challenges faced by higher education institutions. Today's colleges and universities face a plethora of issues ranging from increased demands by traditional and non-traditional students to provide varied and alternative course delivery methods, implementation of new technologies to enhance student learning, faculty issues, budgetary constraints, and increased competition from other institutions leading to decreasing enrollments. Key to meeting these challenges is the mid-level academic administrator. A growing body of literature recognizes the contributions of mid-level academic administrators to the success of the institution. The literature also indicates that the majority of these individuals receive little or no formal training to assist them in meeting the responsibilities and demands of their position. As a result, they are subject to occurrences of role conflict and role ambiguity. A number of programs, however, have been implemented to address these issues. One such program is DeVry University's New Academic Leaders Orientation Program (NALOP). This study examines the effectiveness of the NALOP program from the participants' perspectives immediately after completing the program. Data immediately following the program were analyzed regarding the content, delivery, and materials presented. Participants' perceptions regarding the most useful aspects of the program, least useful aspects of the program, and feelings of confidence in performing as a midlevel administrator after completing the program were analyzed. Results indicated participants were satisfied with the workshop content, delivery, and materials and reported increased feelings of confidence in performing as mid-level administrators. A follow-up questionnaire was sent to the 112 NALOP participants 9 to 40 months after they attended the NALOP workshops. Questionnaires were received from 44 attendees, or a 39% response rate. Results of the data analysis indicated participants felt some degree of role conflict, a low degree of role ambiguity, a medium to high degree of understanding NALOP concepts, and a medium degree of ability to apply NALOP concepts. The results revealed no significant differences between genders, prior employment positions, prior employment affiliations, time elapsed between assuming responsibilities and workshop participation, or workshop formats on role conflict scores, role ambiguity scores, NALOP application scores, or NALOP understanding scores.
Keywords: school administration; higher education; continuing education; educational administration